'Why I Became a Camp Leader?': Insider Views of Camp Leader Candidates - Yalın Aygün; Cemal Gündoğdu; Şakir Tüfekçi; Mehmet Güllü; Mustafa Yılmaz (Selcuk University, 2020)
The aim of this study was to describe individuals' motivation of being camp leader in youth camps of Ministry of Youth and Sport (MYS). Thirteen camp leader candidates who had previously been admitted in the Ministry of Youth and Sports were interviewed using open-ended questions. The data were analyzed using thematic analysis. Analysis resulted in a synthesis of the various ways camp leader candidates were motivated: (a) Self-Actualization and being Beamy, (b) Creating More Leisure and Adventure, (c) Social Integration and, (d) Role Modeling. It is through being volunteer as a camp leader, as we stress, 'that anyone can realize their best selves and find deeper purpose and help others find theirs'. Motivation to be a camp leader is experienced from a perspective of both individualism and social constructivism that shows an interrelated view of freedom, autonomy and also organizational commitment.